2012
DOI: 10.1021/jp209960c
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic and Kinetic Study of CF3CH═CH2+ OH Reaction

Abstract: The potential energy surfaces of the CF(3)CH═CH(2) + OH reaction have been investigated at the BMC-CCSD level based on the geometric parameters optimized at the MP2/6-311++G(d,p) level. Various possible H (or F)-abstraction and addition/elimination pathways are considered. Temperature- and pressure-dependent rate constants have been determined using Rice-Ramsperger-Kassel-Marcus theory with tunneling correction. It is shown that IM1 (CF(3)CHCH(2)OH) and IM2 (CF(3)CHOHCH(2)) formed by collisional stabilization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 42 publications
1
19
0
Order By: Relevance
“…Thomsen and Jorgensen (2009) reported that computed k OH (298 K) for the addition reaction of OH radical with CF 3 CH=CH 2 using DFT, MP2, and CCSD(T) methods was in good agreement with experimental values at 298 K. Recently, Zhang et al (2012) have predicted by multichannel RRKM and transition state theory calculations that k OH (298 K) for reaction 1 was independent of a total pressure between 10 and 10 10 Torr (of Ar and N 2 ). However, the temperature dependence of k OH in Ar between 252 and 370 K experimentally observed by Orkin et al (1997) was not theoretically reproduced by Zhang et al (2012). More recently, Balaganesh and Rajakumar (2014) performed calculations on k OH for reaction 1 at the MP2 and BMC-CCSD levels of theory in the temperature range of 200-3,000 K in accordance with the T dependence reported by Orkin et al (1997).…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…Thomsen and Jorgensen (2009) reported that computed k OH (298 K) for the addition reaction of OH radical with CF 3 CH=CH 2 using DFT, MP2, and CCSD(T) methods was in good agreement with experimental values at 298 K. Recently, Zhang et al (2012) have predicted by multichannel RRKM and transition state theory calculations that k OH (298 K) for reaction 1 was independent of a total pressure between 10 and 10 10 Torr (of Ar and N 2 ). However, the temperature dependence of k OH in Ar between 252 and 370 K experimentally observed by Orkin et al (1997) was not theoretically reproduced by Zhang et al (2012). More recently, Balaganesh and Rajakumar (2014) performed calculations on k OH for reaction 1 at the MP2 and BMC-CCSD levels of theory in the temperature range of 200-3,000 K in accordance with the T dependence reported by Orkin et al (1997).…”
Section: Introductionmentioning
confidence: 82%
“…From the theoretical point of view, reaction 1 has been recently investigated using different theoretical methods (Thomsen and Jørgensen 2009;Zhang et al 2012;Balaganesh and Rajakumar 2014). Thomsen and Jorgensen (2009) reported that computed k OH (298 K) for the addition reaction of OH radical with CF 3 CH=CH 2 using DFT, MP2, and CCSD(T) methods was in good agreement with experimental values at 298 K. Recently, Zhang et al (2012) have predicted by multichannel RRKM and transition state theory calculations that k OH (298 K) for reaction 1 was independent of a total pressure between 10 and 10 10 Torr (of Ar and N 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…For the average energy transferred per collision, <ΔE down >, there is no experimental date available for the target systems in the present work. Vahid et al [37] used a value of 129 cm −1 for CF 3 CF=CF 2 reacting with OH, and Zhang et al [38] used a value of 200 cm −1 in N 2 and 100 cm −1 in Ar for the reactions of CF 3 CH=CH 2 with OH. Considering a heavy Br atom in 2-BTP, we used a temperature-dependent form for this value, that is, <ΔE down > = ΔE 0 (T/300) n (ΔE 0 = 200, n = 0.85).…”
Section: Theoretical Methodologymentioning
confidence: 99%
“…In the present research, by applying steady-state approximation to the activated intermediates and carrying out statistical mechanics manipulations similar to those of Hou et al, expressions for the rate constants of individual channels are derived. Recently, a similar procedure was used by Zhang et al 30 in the theoretical study of the kinetics and mechanism of the CF 3 CHCH 2 + OH reaction. These expressions are discussed in the next sections.…”
Section: ■ Computational Detailsmentioning
confidence: 99%